PENGARUH KUALITAS PELAYANAN TERHADAP LOYALITAS PELANGGAN MELALUI KEPUASAN PELANGGAN PADA RESTAURANT PETERSELI KITCHEN DI KOTA PEKANBARU - ,Hj. Henni Noviasari, Octa Variyani , Jushermi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2023)
This study aims to determine the effect of service quality on customer loyalty through customer satisfaction at the Parsley Kitchen Restaurant in Pekanbaru City. The research method used is quantitative with primary data types in the form of questionnaires and path diagram analysis techniques or path tests. The results of this study indicate that service quality influences customer satisfaction at the Parsley Kitchen Restaurant in Pekanbaru City. Customer satisfaction influences customer loyalty satisfaction in the Parsley Kitchen Restaurant in Pekanbaru City. As well as service quality has an indirect effect on customer loyalty through customer satisfaction. Keywords: Service Quality, Customer Satisfication, Customer Loyalt